2004
DOI: 10.5194/angeo-22-3669-2004
|View full text |Cite
|
Sign up to set email alerts
|

Concerning long-term geomagnetic variations and space climatology

Abstract: Abstract. During geomagnetic polarity transitions the surface magnetic field of the Earth decays to about 25% and less of its present value. This implies a shrinking of the terrestrial magnetosphere and posses the question of whether magnetospheric magnetic field variations scale in the same manner. Furthermore, the geomagnetic main field also controls the magnetospheric magnetic field and space weather conditions. Long-term geomagnetic variations are thus intimately related to space climate. We critically ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 27 publications
1
73
2
Order By: Relevance
“…The question now is to infer how the flux of particles above the South Atlantic and South America will change in response to the evolution of the magnetic field. Glassmeier et al (2004) have shown that less particles can be trapped in a weaker magnetic field. We can also anticipate that interactions between protons trapped in the inner radiation belt and the thermosphere will increase as the SAA grows (Roederer and Zhang (2014)).…”
Section: Discussionmentioning
confidence: 99%
“…The question now is to infer how the flux of particles above the South Atlantic and South America will change in response to the evolution of the magnetic field. Glassmeier et al (2004) have shown that less particles can be trapped in a weaker magnetic field. We can also anticipate that interactions between protons trapped in the inner radiation belt and the thermosphere will increase as the SAA grows (Roederer and Zhang (2014)).…”
Section: Discussionmentioning
confidence: 99%
“…For the geostrophic balance, the scaling law for the size of the magnetic field can be obtained in the following way (Glaßmeier and Vogt 2001). In eq.…”
Section: Magnetic Moment Scaling Lawsmentioning
confidence: 99%
“…For example, Glassmeier et al [2004] examined the effects of long-term geomagnetic variation on the magnetospheric and ionospheric physics and emphasized the importance of the geomagnetic main field in studying the physics. Clilverd et al [2005] reported that a long-term increase in the solar coronal magnetic field strength causes the long trend of the aa index, and thus, the long trend of the Sq field can be at least partly due to solar activity.…”
Section: Introductionmentioning
confidence: 99%